THE EFFECT OF ELECTRIC ENERGY, HUMAN DEVELOPMENT INDEX, AND LABOR ON ECONOMIC GROWTH IN INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Economic growth is one of the main indicators of a country's progress, therefore this study aims to analyze the effect of electrical energy, human development index (HDI), and labor on economic growth in Indonesia. The data used in this study are secondary data in the form of panel data obtained from the annual report of the Central Statistics Agency (BPS) from 2018 to 2022, consisting of 34 provinces in Indonesia. The dependent variable in this study is economic growth, while the independent variables are electrical energy distribution, human development index (HDI), and labor. To determine the effect of electrical energy, human development index (HDI), and labor on economic growth in Indonesia, this study uses the panel data regression analysis method. The results showed that the three variables studied, namely electrical energy, labor and HDI, had a significant effect on economic growth in Indonesia. The variables of electrical energy and labor have a positive and significant effect on economic growth in Indonesia. While the human development index (HDI) variable has a significant negative effect
Keywords: Economic Growth; Electric Energy; Labor